Penyuluhan Bantuan Hukum di Desa Poowo Barat Kecamatan Kabila Kabupaten Bone Bolango - Arsjad, Muh. Fachri; Amu, Robby W.; Rahim, Daud; Nuna, Muten; Ahmad, Rifsal; Olii, Novita; Muko, Kasmawati; Kaku, Beni; Andika, Andika; Bahua, Arman Harun; Bakari, Ade Hikma; Hasim, Safitri Yanti; Deleki, Yurna; Bolota, Febiola (Universitas Gorontalo, 2024)
One of the efforts to improve community legal compliance amid social life is to provide understanding and awareness to implement compliance with aspects that apply in the community. In the implementation of this service activity, the community is provided with knowledge, understanding and awareness of legal aspects, namely by providing legal assistance, which is essentially all efforts to provide legal assistance and services to the community so that they obtain and enjoy all their rights granted by law in the judicial process. The method used is giving theory and direct question and answer. The result of this activity is an increase in the knowledge of individuals and community groups about the awareness of the law in social lifeKeywords: Counseling, Legal Aid, Legal Awareness